En tournant autour du faux - Georges Brunel (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Built in the fourteenth century, remodelled several times, restored by Viollet-le-Duc in the nineteenth century: do the ramparts of Avignon have any claim to authenticity? It is tempting to say “absolutely not”. But this would mean ignoring the fact that authenticity is not an absolute term. It varies according to points of view, many of which exist and all of which must be examined. If we are to avoid sweeping statements, we must closely follow the path from an authentic monument to a restored ruin and then to a fake ruin.